The reinforcement learning workshop learn how to apply cutting-edge reinforcement learning algorithms to a wide range of control problems - Palmas, Alessandro (Packt Publishing Limited, 2020)
bStart with the basics of reinforcement learning and explore deep learning concepts such as deep Q-learning, deep recurrent Q-networks, and policy-based methods with this practical guide/b h4Key Features/h4 ul liUse TensorFlow to write reinforcement learning agents for performing challenging tasks/li liLearn how to solve finite Markov decision problems/li liTrain models to understand popular video games like Breakout/li /ul h4Book Description/h4 Various intelligent applications such as video games, inventory management software, warehouse robots, and translation tools use reinforcement learning (RL) to make decisions and perform actions that maximize the probability of the desired outcome. This book will help you to get to grips with the techniques and the algorithms for implementing RL in your machine learning models. Starting with an introduction to RL, you'll be guided through different RL environments and frameworks.
Keywords: COMPUTERS / Intelligence (AI) & Semantics; COMPUTERS / Neural Networks